(untitled) (NAU Journal of Library and Information Science, 2026)
Reading is a veritable catalyst for achieving societal growth and development. It is the bedrock for a truly great democratic, politically united, economically prosperous and socially organized country. No nation of the world attains any form of development when its people are not literate. This paper defines reading as the process of constructing meaning from written texts. It underscored the importance of reading in societal growth and development. The paper discussed the paradigm shift in reading in 21st Century networked society. It highlighted the constraints for the development of reading culture such as absence of school libraries, lack of conducive and stimulating environment, radical change in value system, harsh economy and high cost of books. Major strategies for the development of reading culture including initiation of family literacy programme, early introduction of children to reading, subsidization of book publishing, promotion of reading culture by libraries and librarians among others were discussed. The paper urged librarians, parents, teachers, publishers and government agencies to work together to build a virile reading nation. It recommends the implementation of the UNESCO minimum benchmark of twenty-six percentage of a country‟s national budgets for education and adequate funding of educational sector by all tiers of government which will help to promote reading culture.